Low‐altitude electron acceleration due to multiple flow bursts in the magnetotail. Issue 3 (15th February 2014) - Nakamura, R.; Karlsson, T.; Hamrin, M.; Nilsson, H.; Marghitu, O.; Amm, O.; Bunescu, C.; Constantinescu, V.; Frey, H. U.; Keiling, A.; Semeter, J.; Sorbalo, E.; et al.
<x xml:space="preserve">Abstract</x> At 10:00 UT on 25 February 2008, Cluster 1 spacecraft crossed the near‐midnight auroral zone, at about 2 RE altitude, while two of the Time History of Events and Macroscale Interactions During Substorms (THEMIS) spacecraft, THD and THE, observed multiple flow bursts on the near‐conjugate plasma sheet field lines. The flow shear pattern at THEMIS was consistent with the vortical motion at duskside of a localized flow channel. Coinciding in time with the flow bursts, Cluster 1 observed bursts of counterstreaming electrons with mostly low energies (≤441 eV), accompanied by short time scale (<5 s) magnetic field disturbances embedded in flow‐associated field‐aligned current systems. This conjugate event not only confirms the idea that the plasma sheet flows are the driver of the kinetic Alfvén waves accelerating the low‐energy electrons but is a unique observation of disturbances in the high‐altitude auroral region relevant to the multiple plasma sheet flows.